Facial soft tissue convexity changes - Hussain A Obaidi; Manar Y Abdul-Qadir (University of Mosul, College of Dentistry, 2007)
Aims: To find the soft tissue changes of the total facial convexity, facial convexity and nasolabial convexity among four age groups. Materials and Methods: The studying sample subjects included 48, 41, 50 and 44 individuals of age 11, 12, 13 and 14 years respectively. The subjects were Iraqi individ-uals of class I normal occlusion, who lived in center of Mosul City. All subjects were radiographed with lateral cephalometric films, these films were traced, the tracing included the total facial convexity (Gl-Prn-Pgs angle), facial convexity (Gl-Sn-Pgs angle) and nasolabial convexity (Cm-Sn-Ls angle). Results: Displayed that the total facial convexity angle in both sexes appeared that no significant change among the four age groups, the facial convexity appeared insignificant differences among the four age groups in males, while in females showed significant increase between the 14 years age group as compared with 11 years age groups, and the nasolabial convexity demonstrated no significant changes among the four age groups for males, whereas in females showed no significant di-fference between 11 and 12 years age group and between 13 and 14 years groups, meanwhile, the 13 and 14 years age group explained significant decrease as compared with 11 and 12 years age groups. The sex variation showed the only significant increase in females than males at 11 years age group for the nasolabial angle. Whereas no significant change between males and females in all the angles at the 12 and 13 years age group. In 14 years age group, the facial convexity angle only showed a significant increase in females as compared with males. Conclusion: No significant change in total facial con-vexity, facial convexity and nasolabial convexity angles among the four age groups in males. Whereas, in females there were a significant increase at 14 years age group, than 11 years age groups for facial convexity and nasolabial convexity angles.